2020
DOI: 10.1093/bioinformatics/btaa010
|View full text |Cite
|
Sign up to set email alerts
|

Network-based prediction of drug–target interactions using an arbitrary-order proximity embedded deep forest

Abstract: Motivation Systematic identification of molecular targets among known drugs plays an essential role in drug repurposing and understanding of their unexpected side effects. Computational approaches for prediction of drug–target interactions (DTIs) are highly desired in comparison to traditional experimental assays. Furthermore, recent advances of multiomics technologies and systems biology approaches have generated large-scale heterogeneous, biological networks, which offer unexpected opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 43 publications
0
76
0
Order By: Relevance
“…After adding its target, an RNA helicase enzyme EIF4A 76 , silvestrol was predicted to be significantly associated with HCoVs (Z = -1.24, P = 0.041) by network proximity analysis. To increase coverage of drug-target networks, we may use computational approaches to systematically predict the drug-target interactions further 25,26 . In addition, the collected virus-host interactions are far from completeness and the quality can be influenced by multiple factors, including different experimental assays and human cell line models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adding its target, an RNA helicase enzyme EIF4A 76 , silvestrol was predicted to be significantly associated with HCoVs (Z = -1.24, P = 0.041) by network proximity analysis. To increase coverage of drug-target networks, we may use computational approaches to systematically predict the drug-target interactions further 25,26 . In addition, the collected virus-host interactions are far from completeness and the quality can be influenced by multiple factors, including different experimental assays and human cell line models.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology allows to identify several candidate repurposable drugs for Ebola virus 11,14 . Our work over the last decade has demonstrated how network strategies can, for example, be used to identify effective repurposable drugs 13,[22][23][24][25][26][27] and drug combinations 28 for multiple human diseases. For example, network-based drug-disease proximity sheds light on the relationship between drugs (e.g., drug targets) and disease modules (molecular determinants in disease pathobiology modules within the PPIs), and can serve as a useful tool for efficient screening of potentially new indications for approved drugs, as well as drug combinations, as demonstrated in our recent studies 13,23,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to use transcriptome technology to uncover the response of bovine mammary epithelial cells (BMEC) to LPS as a way to identify key candidate genes that could be target for functional verification. Along with other assays, a combined technological approach can provide precise targets for research and development of effective therapeutic drugs, ultimately achieving positive effects in terms of prevention and treatment (10).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, this approach can provide precise targets for the research and development of related therapeutic drugs, ultimately achieving the expected combined results of prevention and treatment (15). In the omics study of mastitis, miRNA expression in bovine tissues was first confirmed in 2007 (16).…”
Section: Introductionmentioning
confidence: 99%